Direction and Durability of Causality Between Foreign Institutional Investment and Selected Economic Variables in the Indian Context During Pre and Post Sub-Prime Crisis - Agarwal, Tanu; Geetika; Agrawal, Peeush Ranjan (Indian Journal of Finance, 2017)
The present paper attempted to understand the long-run relationship along with the direction of relationship between foreign institutional investments (FII) and macro-economic variables. For the purpose, three macro variables namely, index of industrial production, exchange rate, and wholesale price index were considered. The data relates to the period from 2003-04 to 2012-13, divided into two durations : pre sub-prime (2003-04 to 2007-08) and post sub-prime (2008-09 to 2012-13) on a monthly basis. The study found a long run equilibrium relationship between set of variables in the pre sub-prime duration ; whereas, this relationship disappeared in the post sub-prime duration. As per the results of Granger’s causality test, no relationship was found between FII net investment and exchange rate, and uni-directional relationship moved from FII net investment to index of industrial production and FII net investment to wholesale price index in the pre sub-prime duration. In the post sub - prime duration, bi-directional causality was found between FII net investment and exchange rate ; whereas, uni-directional relationship was found from index of industrial production to FII net investment and FII net investment to wholesale price index. The main contribution of the research was to study the direction of relationship between FII and macro-economic variables in two; pre sub-prime and post sub-prime durations. Moreover, the direction of causality throws significant light on the behaviour of FIIs in a macro-economic perspective.